Analisis of Sepsis and septic shock 3- and 6-hour management at resuscitation room in Dr,Soetomo General Hospital - Arie Utariani, Arie
Abstract Objective: To provide a record of the implementation and outcome of surviving sepsis campaign 2016 at Dr. Soetomo General Hospital, Surabaya, Indonesia, such as 3-and 6-hour sepsis bundle compliance as a baseline and the Sep-sis-related Organ Failure Assessment (SOFA) score after 48 hours of treatment. SOFA values were used to predict mortality in the hospital. Design: This was an observational experimental study that used cross sectional design. Setting: Resuscitation room in Dr. Soetomo General Hospital. Patients and participants: A purposive sample was taken of patients older than 17-year-old suspected with sepsis or septic shock according to diagnosis criteria from Surviving Sepsis Campaign (SSC) 2016. Thirty-two patients, consist of 24 male and 8 female patients were included. Interventions: After patients were suspected of sepsis or septic shock according to diagnosis criteria from SSC 2016, they were treated with 3-and 6-hour sepsis bundle, then the data were collected with questionnaire. Measurements and results: We found 75% of patients received a 3-hour sepsis bundle in <3 hours, and 50% of patients had 6-hour sepsis bundle in <6 hours. The compliance rate of 3-and 6-hour sepsis and septic shock bundles reached 46.88%. SOFA scores before and after 48-hour management of sepsis had a significant increase with p=0.001 (p<0.05). Conclusions: There were significant decreasing of SOFA values in baseline and 48 hours after the management of sepsis and septic shock in 81.25% patients (n=26). This result suggests that management of sepsis based on SSC 2016 contribute to the improvement of the patient's condition and better prognosis.